Home‐based early intervention in infants and young children with visual impairment using the Developmental Journal: longitudinal cohort study. (13th November 2018) - Dale, Naomi J; Sakkalou, Elena; O'Reilly, Michelle A; Springall, Clare; Sakki, Hanna; Glew, Sarah; Pissaridou, Eleni; De Haan, Michelle; Salt, Alison T
Abstract : Aim: To investigate the effects of home‐based early intervention in children with severe visual impairment (SVI) using the Developmental Journal for babies and young children with visual impairment (DJVI). Method: A longitudinal observational study was undertaken with a national cohort (OPTIMUM) of infants with congenital disorders of the peripheral visual system (CDPVS) and profound‐SVI; and followed up after 12 months and 24 months. Intervention was categorized according to the practitioner diary records of their usual practice over 12 months from baseline comparing those receiving the DJVI and those receiving 'Other Support'. Outcome measures of cognition and language, behaviour difficulties, parenting stress, and satisfaction with parent–practitioner partnership were collected. Results: In the 54 children (26 males, 28 females, baseline mean age 13.5mo, SD 2.3mo, range 8–17mo) with 'total' CDPVS (including 16 'complex' and 38 'simple' with or without known brain disorder respectively), linear mixed effects pointed towards acceleration in sensorimotor understanding and expressive language especially in the 'simple' subsample (11.72 developmental quotient, 95% confidence interval −1.17 to 24.61, p >0.05) in those receiving the DJVI. Vision level also predicted outcomes ( p <0.05). The DJVI group showed improvements in behavioural withdrawal ( η 2 =0.20, p =0.02, 'simple') and parenting stress ( d =0.78, d =0.92, p =0.02 total and 'simple' respectively) and perceived practitioner–parent relationship ( η 2 =0.16, p =0.01). Interpretation: Infants and young children with visual impairment receiving home‐based early intervention using the DJVI with a structured developmental approach had better outcomes than those receiving 'other' home‐based early interventions. Moderate to large effect improvements were found in child cognition and language, behaviour and parenting stress and the perceived practitioner‐parent relationship, although cognition did not reach 5% significance level. What this paper adds: Early intervention using the Developmental Journal for babies and young children with visual impairment was associated with enhanced developmental outcomes compared to other approaches. Improvements were also found in child behaviour, parenting stress, and perceived parent practitioner outcomes. Type and complexity of visual impairment also influenced outcomes. What this paper adds: Early intervention using the Developmental Journal for babies and young children with visual impairment was associated with enhanced developmental outcomes compared to other approaches. Improvements were also found in child behaviour, parenting stress, and perceived parent practitioner outcomes. Type and complexity of visual impairment also influenced outcomes. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Deramore Denver on page 627 of this issue. Resumen: Intervención temprana domiciliaria en lactantes y niños pequeños con discapacidad visual usando el Diario de Desarrollo: estudio longitudinal de cohorte: Objetivo: Investigar los efectos de la intervención temprana en el hogar en niños con discapacidad visual grave utilizando el Diario de Desarrollo para bebés y niños pequeños con discapacidad visual (DJVI). Método: Se realizó un estudio observacional longitudinal con una cohorte nacional (OPTIMUM) de bebés con trastornos congénitos del sistema visual periférico (CDPVS) y discapacidad visual profunda‐severa; y seguimiento después de 12 meses y 24 meses. La intervención se categorizó de acuerdo con los registros del diario de desarrollo del médico en su práctica habitual más de 12 meses desde el inicio, comparando los que recibieron el DJVI y los que recibieron "otro apoyo". Se recopilaron las medidas de resultado de la cognición y el lenguaje, las dificultades de comportamiento, el estrés de los padres y la satisfacción con la asociación entre padres y profesionales. Resultados: En los 54 niños (26 varones, 28 mujeres, edad media de referencia 13, 5 meses, DS 2, 3 meses, rango 8–17 meses) con CDPVS 'total' (incluidos 16 'complejo' y 38 'simple' con o sin trastorno cerebral conocido respectivamente), los efectos mixtos lineales apuntan hacia la aceleración en la comprensión sensoriomotora y el lenguaje expresivo, especialmente en la submuestra "simple" (cociente de desarrollo 11, 72, intervalo de confianza del 95% –1, 17 a 24, 61, p >0, 05) en los que recibieron el DJVI. El nivel de visión también predijo resultados (p <0, 05). El grupo DJVI mostró mejoras en la abstinencia conductual ( η 2 =0, 20, p =0, 02, 'simple') y el estrés parental ( d =0, 78 − d =0, 92, p =0, 02 total y 'simple' respectivamente) y la relación percibida entre el médico y el padre ( η 2 =0, 16, p =0, 01). Interpretación: Los bebés y niños pequeños con discapacidad visual que recibieron una intervención temprana en el hogar utilizando el DJVI, con un enfoque de desarrollo estructurado, tuvieron mejores resultados que los que recibieron "otras" intervenciones tempranas en el hogar. Se encontraron mejoras de efecto moderado a grande en la cognición infantil y el lenguaje, el comportamiento y el estrés parental y la relación percibida entre el médico y el padre, aunque la cognición no alcanzó el nivel de significación del 5%. Resumo: Intervenção precoce domiciliar em lactentes e crianças jovens com deficiência visual usando o Developmental Journal: estudo de coorte longitudinal: Objetivo: Investigar os efeitos da intervenção precoce domiciliar em crianças com deficiência visual severa usando o Developmental Journal para lactentes e crianças jovens com deficiência visual (DJDV). Metodo: Um estudo observacional longitudinal foi realizado com uma coorte nacional (OPTIMUM) de crianças com distúrbios congênitos do sistema visual periférico (DCSVP) e deficiência visual grave‐profunda, estes foram acompanhados após 12 meses e 24 meses. A intervenção foi categorizada de acordo com os registros diários do profissional de sua prática habitual ao longo de 12 meses, a partir de uma linha de base, comparando aqueles que receberam a DJDV e os que receberam "outro suporte". Resultados dos testes de cognição e linguagem, dificuldades de comportamento, estresse parental e satisfação com a parceria entre pais e profissionais, foram coletados. Resultados: Nas 54 crianças (26 do sexo masculino e 28 do feminino, média de idade na linha de base de 13, 5 meses; DP 2, 3 meses; variação de 8 a 17 meses) com DCSVP total (incluindo 16 'complexos' e 38 'simples' com ou sem distúrbio cerebral conhecido, respectivamente), efeitos mistos lineares apontaram para um avanço na compreensão sensório‐motora e de linguagem expressiva, especialmente, no subgrupo 'simples' (11, 72 quociente de desenvolvimento, IC 95% –1, 17 a 24, 61; p >0, 05) naqueles que receberam o DJDV. Nível visual também foi preditivo dos desfechos ( p <0, 05). O grupo DJDV apresentou melhora no comportamento de retraimento social ( η 2 =0, 20; p =0, 02; 'simples'), no estresse parental ( d =0, 78 − d =0, 92; p =0, 02 total e 'simples', respectivamente) e na percepção do relacionamento profissional‐pais ( η 2 =0, 16; p =0, 01). Interpretação: Lactentes e crianças jovens com deficiência visual que recebem intervenção domiciliar precoce usando a DJVI com uma abordagem de desenvolvimento estruturado tiveram resultados melhores do que aqueles que receberam "outras" intervenções precoces em casa. Melhorias com efeito de moderado a grande foram encontradas na cognição e linguagem, no comportamento infantil e estresse parental, e no relacionamento percebido entre pais e profissionais, embora a cognição não tenha alcançado nível de significância de 5%.